Systematic Review of Cognitive Function in Euthymic Bipolar Disorder and Pre-Surgical Temporal Lobe Epilepsy - Bostock, Emmanuelle C. S.; Kirkby, Kenneth C.; Garry, Michael I.; Taylor, Bruce V. M. (Frontiers in Psychiatry, 2017)
Background Bipolar disorder and temporal lobe epilepsy (TLE) overlap in domains including epidemiology, treatment response, shared neurotransmitter involvement and temporal lobe pathology. Comparison of cognitive function in both disorders may indicate temporal lobe mediated processes relevant to bipolar disorder. This systematic review examines neuropsychological test profiles in euthymic bipolar disorder type I (BD¬–I) and pre-surgical TLE and compares experimental designs used. Methods A search of PubMed, PsychINFO and Scopus using PRISMA guidelines was conducted. Inclusion criteria were comparison group or pre- to post-surgical patients; reported neuropsychological tests; participants aged 18-60. Fifty six studies met criteria: 27 BD–I; 29 TLE. Results Deficits in BD–I compared to healthy controls were in executive function, attention span and verbal memory. Deficits in TLE compared to healthy controls (HC) were in executive function and memory. In the pre- to post-surgical comparisons, verbal memory in left temporal lobe (LTL) and, less consistently, visuospatial memory in right temporal lobe (RTL) epilepsy declined following surgery. BD–I studies used comprehensive test batteries in well-defined euthymic patients compared to matched HC groups. TLE studies used convenience samples pre- to post-surgery, comparing LTL and RTL subgroups, few included comparisons to HC (5 studies). TLE studies typically examined a narrow range of known temporal lobe mediated neuropsychological functions, particularly verbal and visuospatial memory. Conclusions Both disorders exhibit deficits in executive function and verbal memory suggestive of both frontal and temporal lobe involvement. However deficits in TLE are measured pre- to post-surgery and not controlled at baseline pre-surgery. Further research involving a head-to-head comparison of the two disorders on a broad range of neuropsychological tests is needed to clarify the nature and extent of cognitive deficits and potential overlaps.